Computational Fluid Dynamics Study Of Nasal Cavity Model - Riazuddin, Vizy Nazira (2011)
Understanding the properties of airflow in the nasal cavity is very important in determining the nasal physiology and in diagnosis of various anomalies associated with the nose. Inter-human anatomical variation for the nasal cavity exists and also differences on physiological morphology are observed based on gender. No specific numerical modeling studies have been carried out to compare and ascertain the effect of gender on flow variable inside the nasal cavity. Also numerical modeling involves various simplifications, for example the postural effect and appropriate boundary conditions which affect the outcome of the airflow studies.